Bioinformatic and functional characterization of cyclic-di-GMP metabolic proteins in Vibrio alginolyticus unveils key diguanylate cyclases controlling multiple biofilm-associated phenotypes - Gong, Xiao-Xiao; Zeng, Yan-Hua; Chen, Hai-Min; Zhang, Na; Han, Yue; Long, Hao; Xie, Zhen-Yu (Frontiers in Microbiology, 2023)
The biofilm lifestyle is critical for bacterial survival and proliferation in the fluctuating marine environment. Cyclic diguanylate (c-di-GMP) is a key second messenger during bacterial adaptation to various environmental signals, which has been identified as a master regulator of biofilm formation. However, little is known about whether and how c-di-GMP signaling regulates biofilm formation in Vibrio alginolyticus, a globally dominant marine pathogen. Here, a large set of 63 proteins were predicted to participate in c-di-GMP metabolism (biosynthesis or degradation) in a pathogenic V. alginolyticus strain HN08155. Guided by protein homology, conserved domains and gene context information, a representative subset of 22 c-di-GMP metabolic proteins were selected to determine which ones affect biofilmassociated phenotypes. By comparing phenotypic differences between the wild-type and mutants or overexpression strains, we found that 22 c-di-GMP metabolic proteins can separately regulate different phenotypic outputs in V. alginolyticus. The results indicated that overexpression of four c-di-GMP metabolic proteins, including VA0356, VA1591 (CdgM), VA4033 (DgcB) and VA0088, strongly enhanced rugose colony morphotypes and strengthened Congo Red (CR) binding capacity, both of which are indicators of biofilm matrix overproduction. Furthermore, rugose enhanced colonies were accompanied by increased transcript levels of extracellular polysaccharide (EPS) biosynthesis genes and decreased expression of flagellar synthesis genes compared to smooth colonies (WTpBAD control), as demonstrated by overexpression strains WTp4033 and ∆VA4033p4033. Overall, the high abundance of c-di-GMP metabolic proteins in V. alginolyticus suggests that c-di-GMP signaling and regulatory system could play a key role in its response and adaptation to the ever-changing marine environment. This work provides a robust foundation for the study of the molecular mechanisms of c-di-GMP in the biofilm formation of V. alginolyticus.